Assessment of Factors Influencing the Effective Implementation of Public Projects: The Case of Selected Public Projects Financed by Botor Tolay Woreda Administration, Oromia Regional State, Ethiopia - Susi, Elias (Journal of Public Policy and Administration, 2023)
Purpose: The main purpose of the study was to assess the factors that influence the effective Implementation of public projects: The Case of Botor Tolay Woreda, Oromia Regional State, Ethiopia. Methodology: The study was both descriptive and explanatory research design and applied Quantitative and qualitative research approach. The primary and secondary data was used, the primary data was collected by using questionnaires and observation while the secondary data was through analysis the documents. Purposively select 26 expertise and experienced employee from the government office and Contractors. The collected data was analyzed by using descriptive and inferential statistics. To ensure the relationship between independent and dependent variables the Pearson correlation and multiple linear regression was applied. The data was analyzed by using Statistical package for Social Science (SPSS) version 25. The study Result was presented through the using of table and figures. Finding: The study focuses on the four major factors that affecting the success of public project implementation those planning and scope cause of delays, Client related, Contractor related and external factor related delays of the public project implementation. The findings of correlation and regression show that there was a positive and significant relationship between Project implementation and, Planning and scope of the project, Client, Contractor and external factor related delays. Unique Contribution to Theory, Practice and Policy: The researcher recommended that the government body open consulting and supervising office of construction at woreda level for delays of payment approval to successful implementation of the public project, The woreda also practice by improving the delays of client, and planning and scope level delays, the contractor practice their work as schedule, cost and quality.Both government body and contractor develop the methods of resisting the external factors to compact the problemsystems, stakeholder, agency, institutional, and resource dependency theories.